Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan PPKn Model Printer Pada Siswa Kelas IV SDN Tanjung Pagar 3 Banjarmasin - Maulana Ahmad Zailani; Dessy Dwitalia Sari (CV. ITTC INDONESIA, 2024)
The issue emphasized in this study is the lack of student participation in activities and limited learning achievements. The root of this problem lies in the insufficient focus on students in the learning process, low student engagement in activities, and limited academic performance. Therefore, one of the steps to enhance engagement and learning achievements is through the implementation of problem-based learning models, Think Pair Share, and Picture and Picture. The purpose of this research is to depict the activities of educators and students, as well as to analyze the learning achievements of the students. The approach utilized in this research is a qualitative approach with the type of Classroom Action Research, carried out over four sessions. The focus group of this research comprises students from Class IV of SDN TANJUNG PAGAR 3 in the Academic Year 2023/2024, totaling 33 students. The method of analysis employed involves observation, while data regarding students' learning achievements are obtained through assessment, which is subsequently analyzed using descriptive approaches and illustrated in the form of tables and diagrams. The research findings indicate that in the first meeting, educators' activities reached the